2021
DOI: 10.1002/ehf2.13441
|View full text |Cite
|
Sign up to set email alerts
|

Heart failure associated with imported malaria: a nationwide Danish cohort study

Abstract: Aims Despite adequate treatment, recent studies have hypothesized that malaria may affect long-term cardiovascular function. We aimed to investigate the long-term risk of cardiovascular events and death in individuals with a history of imported malaria in Denmark. Methods Using nationwide Danish registries, we followed individuals with a history of malaria for the risk of incident heart failure (HF), myocardial infarction (MI), cardiovascular death and all-cause death (1 January 1994 to 1 January 2017). The po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Prior studies have indicated that some types of NCDs may be associated with malaria and malaria severity [16][17][18]. A Danish study found that malaria may be associated with cardiac complications, and people with malaria history may carry out a long-term risk of cardiovascular conditions and deaths [21]. Two recent studies also have suggested that long-term malaria exposure is linked to cardiovascular events, especially hypertension [17,34] Moreover, Kalra et al suggested that malaria has been more common in diabetes mellitus [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have indicated that some types of NCDs may be associated with malaria and malaria severity [16][17][18]. A Danish study found that malaria may be associated with cardiac complications, and people with malaria history may carry out a long-term risk of cardiovascular conditions and deaths [21]. Two recent studies also have suggested that long-term malaria exposure is linked to cardiovascular events, especially hypertension [17,34] Moreover, Kalra et al suggested that malaria has been more common in diabetes mellitus [19].…”
Section: Discussionmentioning
confidence: 99%
“…In several studies from Africa, malaria has been documented to be more common in people with diabetes [19]. In addition, few experimental studies have also shown that malaria may affect blood pressure and induce hypertension, which contributes to heart failure [20,21]. However, there are few studies on the trends in the burden of NCDs in countries with the highest malaria burden from the perspective of epidemiological transition.…”
Section: Introductionmentioning
confidence: 99%
“…This is thought to occur through the chronic inflammation and endothelial dysfunction that can result from repeated or chronic malaria infections [ 120 , 121 ]. Brainin et al conducted a cohort study in Denmark and found that individuals with Plasmodium infections had an increased risk of heart attack [ 122 ]. Cardiovascular complications in malaria are mainly attributed to the altered cytoadhesive properties of P. falciparum -infected erythrocytes.…”
Section: Immune Evasion In the Vertebrate Hostmentioning
confidence: 99%
“…Although these hospitals are not easily accessible to high-risk groups in communities endemic to malaria, it is crucial to have accurate and comprehensive data on malaria patients and their subsequent hospital medical information to optimize patient care in terms of a life-course approach, and to monitor the impact of program interventions on vulnerable populations. Nevertheless, most of the RWD studies reported are focused on imported malaria in European countries [15][16][17]. Furthermore, only a few observational cohort studies regarding MDP patients have been reported using patient clinical data [18,19].…”
Section: Introductionmentioning
confidence: 99%